Antioksidan Beluntas (Jurnal Teknologi Pangan, 2013)
Beluntas  (Pluchea  indica  Less)  is  a  herb  that  commonly  used  as  traditional medicine  and  food.    Its  leaves  have  many  biological  activities,  because  they  contain various  phenolic  compounds.  The  phenol  concentration  of  beluntas  leaves  depends on leaf segment, earth condition, fertilizer and environmental stress.  This research is focused  to  determine   antioxidant  activity  of  three  groups  of    beluntas  leaf  segments that   includes 1-3, 4-6 and > 6.  They were ground, dried at ambient temperature for  7  days, maserated by petroleum eter (1:4 b/v) at ambient temperature for 24 hours and soxhlet  extracted  by  methanol  (1:15  b/v)  at  65oC  for  3   hours.  The  result  shows  that the  extract  contains  phytochemical   compounds  such  as  tannin,  sterol,  phenol hydroquinone  and  flavonoid.  This  extract  has  antioxidant  activity  to  scavenging  free radical  DPPH   (2,2-phenyl-1-picrylhydrazyl).  The extract of  1-3  beluntas  leaf  segment  was   more  potential  antioxidant  source  than  4-6  and  >  6  beluntas  leaf   segments,  because it had the least IC50 (inhibitor concentration) and the  highest total phenol and  total flavonoid. The IC50, total  phenol and flavonoid  total of  it were 3.71 mg/L,  234.65  mg GAE/100 g samples  and 2163.59 mg QE/ 100 g samples, respectively.